2006
DOI: 10.1056/nejmoa052955
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Autoantibodies to the PDGF Receptor in Systemic Sclerosis

Abstract: Stimulatory autoantibodies against PDGFR appear to be a specific hallmark of scleroderma. Their biologic activity on fibroblasts strongly suggests that they have a causal role in the pathogenesis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
121
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 520 publications
(140 citation statements)
references
References 13 publications
6
121
1
5
Order By: Relevance
“…10 We have recently shown that patients with cGVHD showing fibrotic/sclerotic manifestations have agonistic antibodies activating the platelet-derived growth factor receptor (PDGF) receptor. 11 The presence and biologic activity of these autoantibodies argue for a common pathogenic trait in both cGVDH and SSc, 11,12 in that up-regulation of the PDGF receptor intracellular pathway leads to increased reactive oxygen species, with consequent exaggerated collagen synthesis, which, in turn, contributes to the pathologic lesions observed in both cGVHD and SSc.…”
Section: Introductionmentioning
confidence: 99%
“…10 We have recently shown that patients with cGVHD showing fibrotic/sclerotic manifestations have agonistic antibodies activating the platelet-derived growth factor receptor (PDGF) receptor. 11 The presence and biologic activity of these autoantibodies argue for a common pathogenic trait in both cGVDH and SSc, 11,12 in that up-regulation of the PDGF receptor intracellular pathway leads to increased reactive oxygen species, with consequent exaggerated collagen synthesis, which, in turn, contributes to the pathologic lesions observed in both cGVHD and SSc.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies that activate PDGFRs are present in sera of patients with scleroderma and are implicated in facilitating the fibrotic component of this pathology (4). Growth factors outside the PDGF family (PDGFs) are present in vitreous (the viscous fluid that fills the space between the lens and retina) from patients with proliferative vitreoretinopathy (PVR) and trigger indirect activation of PDGF receptor ␣ (PDGFR␣), which is a key event in the pathogenesis of this fibroproliferative disease in animal models (5).…”
mentioning
confidence: 99%
“…Предполагается стимуляторный про-фиброзный эффект антител к РТФР, поскольку их связы-вание с лигандом приводит к активации фибробластов и последующей гиперпродукции реактивных кислородных радикалов (РКР), которые, в свою очередь, поддерживают фибробласты в состоянии активации, стимулируя проли-ферацию клеток и синтез компонентов внеклеточного ма-трикса [93]. Авторы обнаружили антитела к РТФР у всех больных ССД, но не у здоровых лиц, больных СКВ, РА, идиопатическим легочным фиброзом и первичным фено-меном Рейно.…”
Section: ау тоантитела к поверхностным клеточным (мембранным) и вunclassified